Utilisation of E-Resources to Support Teaching and Research in Higher Learning Institutions, Tanzania - Mwantimwa, Kelefa T; Elia, Emmanuel; Ndenje-Sichalwe, Esther (University of Dar es Salaam Library Journal, 2018)
This study was conducted to compare the use of electronic information resources in selected universities in Tanzania. The study employed a mixed methods research approach to collecting, processing, analysing data and discussing the resultant findings. In all, 119 academic staff and researchers participated in the study. SPSS and STATA were used to analyse the data. The key findings suggest that the majority of academic staff and researchers were aware of, have access to and utilise e-resources to support teaching and research. On the whole, the study found a significant and positive association between awareness and access, access and use. In fact, most of the e-resources the selected higher learning institutions subscribed to through COTUL were under-utilised. Apart from information literacy skills, personal motivations and e-resource infrastructures, demographic characteristics such as age and education level of academic staff and researchers are predictors in e-resources usage. Furthermore, the challenges and problems that deter the effective utilisation of e-resources were include slow internet connectivity, inability to access full-text articles, unreliable power supply, inaccessibility of e-resources outside university premises due to IP address limitations, inadequate ICT infrastructure and inadequate skills and knowledge. The study found that there was a need to promote the usage of e-resources through web technologies to enhance the quality of teaching and research.